Environmental and genetic trends in clean fleece mass, live mass and fiber diameter in selection and control flocks involving a selection experiment for increased clean fleece mass in South African Merino sheep - Cloete, S.W.P.; Delport, G.J.; Erasmus, G.J.; Olivier, J.J.; Heydenrych, H.J.; Toit, Elizabeth du (1992)
This study was undertaken to investigate the genetic stability of an unselected Conlrol Group of South African Merino sheep and genetic change in a flock selected for increased clean fleece mass (Selection Group) under the same environmental conditions. Data regarding 14-17 months clean fleece mass (CFM) and fibre diameter (FD) of 5867 progeny from these groups (3186 and 2681 individuals in the Selection and Conlrol Groups, respectively) were analysed to investigate genetic change over the period 1969-1989. A smaller data set, involving 5273 progeny (2782 and 2491 individuals in the respective groups) born in 1971-1989, was used to investigate change in 16-17 month live mass (LM). An animal model was used to obtain predicted breeding values (PBVs) for all individuals by mixed model analysis (MMA). Average PBVs of Selection and Conlrol group progeny within birth years were taken as a measure of genetic change, rendering genetic trends independent from environmental bias. Genetic change in the Selection Group was also obtained by deviating average PBVs from those obtained in the Control Group. This approach is analogous to the method of expressing genetic change as least squares deviations of Selection Group progeny from Control Group contemporaries, and will be affected by genetic change in the Control Group. Prior heritability estimates, derived for the MMA by paternal halfsib procedures, were within ranges reported in the literature. Year-to-year variation, as derived from environmental trends from the MMA, appeared to be less for FD when compared to LM and CFM. Average PBVs for Control Group progeny increased (P